2017
DOI: 10.1007/s11605-016-3231-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-Elective Paraesophageal Hernia Repair Portends Worse Outcomes in Comparable Patients: a Propensity-Adjusted Analysis

Abstract: Introduction Patients undergoing non-elective paraesophageal hernia repair (PEHR) have worse perioperative outcomes. Because they are usually older and sicker, however, these patients may be more prone to adverse events, independent of surgical urgency. Our study aimed to determine whether non-elective PEHR is associated with differential postoperative outcome compared to elective repair, using propensity-score weighting. Methods We abstracted data for patients undergoing PEHR (n=924; non-elective n=171 [19%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The authors analyzed 980 patients at a single institution, and found that even when accounting for baseline patient characteristics, emergent repair was associated with worse outcomes when compared with elective repair. 24 Similarly, a study by Jassim et al surveyed a nationwide inpatient sample, and found that emergent repair was associated with higher rates of morbidity and mortality when compared with elective patients. 7…”
Section: Discussionmentioning
confidence: 99%
“…The authors analyzed 980 patients at a single institution, and found that even when accounting for baseline patient characteristics, emergent repair was associated with worse outcomes when compared with elective repair. 24 Similarly, a study by Jassim et al surveyed a nationwide inpatient sample, and found that emergent repair was associated with higher rates of morbidity and mortality when compared with elective patients. 7…”
Section: Discussionmentioning
confidence: 99%
“…The latter is justified from the mortality rate that emergent repair poses. Another very interesting study, claimed that 'non-elective repair was independently associated with 1.7 times increased odds of major adverse events and trended toward an increase of 2.7 times for odds of mortality compared to elective repair, after accounting for age and comorbid index score (23). Emergency repair of a large paraesophageal HH is associated with increased morbidity in comparison with elective surgery, in a study of the American College of Surgeons National Surgical Quality Improvement Program, including 383 patients (16% versus 1.6%) (22).…”
Section: Resultsmentioning
confidence: 99%
“…Acute complications in PEH are surgical emergency; both laparoscopic and open approach have been used and debate also exists as to which approach is preferable. Patients undergoing emergent surgery for hiatal hernia repair have more adverse prognostic factors and more major complications (38 versus 18%; p < 0.001) and deaths (8 versus 1%; p < 0.001) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%